Insights into the Electrochemistry of the Deposition of Boron from KCl-KF-NaBF4 Melt - Pala,Rahul (2014)
Electrochemical reduction of boron from boron containing fluoroborate species present in KCl (81.54 mol%)-KF (18.45 mol%)-NaBF4 (1.67 × 10-4 mol cm-3) melt on a platinum electrode was studied by cyclic voltammetry and chronoamperometry. These studies were carried out over the temperature range 1073 - 1123 K. Boron-containing electroactive species is shown to reduce quasi-reversibly at low scan rates (v < 0.1 V s-1) and irreversibly at higher scan rates (v > 0.1 V s-1) through a single-step three-electron process (B(III) + 3e- → B). The transfer and diffusion coefficients of the electroactive species were measured for sodium fluoroborate in KCl-KF melt over the temperature range 1073 - 1123 K.